PENGARUH PEMBERIAN MUSIK BINAURAL BEAT TERHADAP KEMAMPUAN MEMORI JANGKA PENDEK MELALUI ANALISIS GELOMBANG OTAK MENGGUNAKAN MUSETM EEG - Fauzan Fadhlurrahman, Rifky
Memory is a key element in most cognitive functions and has a limited capacity to store information. Short-term memory (STM) has an important relationship with activities associated with individual awareness and attention processes. Music is known to stimulate and improve memory and brain waves as well as balance left - right brain activity to help concentration power. Binaural beat music plays a role in the process of regulating the level of alertness, concentration and focus of individual attention. The use of electroencephalogram (EEG) technology can provide information about brain wave activity related to cognitive processes when given music treatment. The purpose of this study was to determine the effect of binaural beat music on beta, alpha and theta brain wave activities when carrying out a series of STM tests, by comparing the activity of brain wave channels that can be distinguished based on the location of the hemispheres and lobes of the brain. The research method used qualitative – semi-quantitative analysis involving 10 male student participants (aged 20-24 years). Participants filled out questionnaires at the beginning and end of the session, and between the two sessions, the STM test was carried out followed by listening to binaural beat (BB) music and without listening to music (TM) for 3 minutes each. The treatment was divided into two types, namely: type 1 begins with BB treatment followed by TM and type 2 begins with TM treatment followed by BB. The phase of giving BB and TM music was further divided into 3 stages, namely: (1) resting-pre, (2) STM-Test and (3) resting-post. Two different types of questions were given during the STM test, namely: (1) questions with 8 digits of letters and numbers and (2) questions with 10 digits of letters and numbers. The data generated was the logarithm of Power Spectral Density of each wave measured on each EEG sensor in the temporoparietal (TP9, TP10) and anterofrontal (AF7, AF8) lobes. The results showed that the mean of beta, alpha and theta waves in the BB treatment on the TP > AF wave channel. The BB treatment showed that the right hemisphere had more significant effect than the TM treatment on each Keywords: Music binaural beat, short-term memory, beta brainwave, alpha brainwave, theta brainwave, MuseTM EEGbeta, alpha and theta waves with p<0.05. Furthermore, the results of the analysis of the STM test showed that the treatment of BB > TM when the STM-Test was given. The highest beta, alpha and theta brain wave activity values were at the resting-post test stage. Treatment type 1 showed a non-significant difference (p>0.05), while treatment type 2 showed a significant difference (p<0.05). However, the increase in the average value of each brain wave activity was not significant difference. The results of BB treatment were significantly different in the theta wave (p<0.05), but in beta and alpha waves were not significantly different (p>0.05). Analysis of cognition while listening to music and completing the short-term memory test indicated that the effect of giving music on audiovisual abilities and theta brainwave activity was more significant than beta and alpha brain waves.